واقع استخدام طلبة الدِّراسات العليا في جامعة دمشق للمكتبات الرَّقمية - ديب, أوصــاف علي; يحيــــى, يـــارا بسَّـــــام (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
هدفَتْ الدِّراسة إلى تعرُّف واقع استخدام طلبة الدِّراسات العليا في جامعة دمشق للمكتبات الرَّقمية. في ضوء متغيراتٍ: (الجنس، التَّخصص، الخضوع لدوراتٍ تدريبية في مجال الانترنت).وَتمَّ استخدام المنهج الوصفي التَّحليلي باعتباره المنهج المناسب لتحقيق أهداف هذه الدِّراسة، كما تمَّ إعداد استبانة طبقت على عينة عشوائية بلغَتْ(40) طالباً وَطالبةً من طلبة الدِّراسات العليا في كليتَي (التَّربية وَالهندسة الزِّراعية)في جامعة دمشق.وَتوصلَتْ الدِّراسة إلى النَّتائج الآتية: • وجود فرق ذ ي دلالة إحصائية عند مستوى دلالة (0,05%)بين متوسطات درجات طلبة الدِّراسات العليا على محوري (الاستخدام وَالأهميَّة)تبعاً لمتغير التَّخصص لصالح تخصص التَّربية.• عدم وجود فرق ذي دلالة إحصائية عند مستوى دلالة (0,05%) بين متوسطات درجات طلبة الدِّراسات العليا على محاور الاستبانة تبعاً لمتغير الجنس.• عدم وجود فرق ذي دلالة إحصائية عند مستوى دلالة (0,05%) بين متوسطات درجات طلبة الدِّراسات العليا على محاور الاستبانة تبعاً لمتغير الخضوع لدوراتٍ تدريبيةٍ في مجال الانترنت. The aim of the research is to find out the usage reality of postgraduate students at Damascus University of digital libraries. In light of the variables:(Gender, Scientific major, getting training courses).The research methodology:A descriptive analyticalapproach.The researcher designed &prepared the research tool which is a questionnaire that was applied on a random sample consisting of (40) postgraduates (male & female) in different faculties of Damascus University. The study reached the following results:- There is a statistically significant difference at the significance level of (0,05)between the mean scores of postgraduate students in the faculties of Damascus University of the following variables: Concentration.-There is no statistically significant difference at the significance level of(0,05) between the mean scores of postgraduate students in the facultiesof Damascus University of the following variables: Gender.-There is no statistically significant difference at the significance level of (0,05)between the mean scores of postgraduate students in the colleges of Damascus University of the following variables: getting training courses.